2005
DOI: 10.1161/01.hyp.0000154365.30593.d3
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Activates Vascular p38MAP Kinase and NADPH Oxidase Via c-Src

Abstract: Abstract-Increasing evidence indicates that aldosterone elicits vascular effects through nongenomic signaling pathways.We tested the hypothesis that aldosterone induces activation of vascular mitogen-activated protein (MAP) kinases and NADPH oxidase via c-Src-dependent mechanisms in vascular smooth muscle cells (VSMCs). Aldosterone effects on activation of c-Src, p38MAP kinase, and NADPH oxidase, and incorporation of [ 3 H]proline, an index of collagen synthesis, were assessed in cultured rat VSMCs. Studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
206
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(219 citation statements)
references
References 40 publications
11
206
0
2
Order By: Relevance
“…Recent basic studies have reported that aldosterone promoted the inflammatory state through Src and p38 mitogen-activated protein kinases and NADPH oxidase activation in vascular smooth muscle cells. 23,24 Furthermore, Suzuki et al 31 showed that although mineralocorticoid receptor blockade did not affect BP in male apolipoprotein E-deficient mice, it decreased the inflammatory response. Together with our study and those reports, the CYP11B2 C-344T polymorphism, as well as aldosterone itself, may possibly have direct effects on the systemic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent basic studies have reported that aldosterone promoted the inflammatory state through Src and p38 mitogen-activated protein kinases and NADPH oxidase activation in vascular smooth muscle cells. 23,24 Furthermore, Suzuki et al 31 showed that although mineralocorticoid receptor blockade did not affect BP in male apolipoprotein E-deficient mice, it decreased the inflammatory response. Together with our study and those reports, the CYP11B2 C-344T polymorphism, as well as aldosterone itself, may possibly have direct effects on the systemic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Serum C-reactive protein (CRP) levels can reflect the severity of vascular or myocardial inflammation, 25,26 and some clinical studies have shown that elevated serum CRP levels in healthy populations are predictive of vascular events, such as myocardial infarction and stroke. 27,28 Although the association of aldosterone with inflammation has been established, there are no reports on the relationship between the CYP11B2 C-344T polymorphism and the serum levels of inflammatory markers such as CRP.…”
Section: Introductionmentioning
confidence: 99%
“…50 -52 Phosphorylation of c-Src and p38MAP kinase phosphorylation, NADPH oxidase activation, and protein synthesis were dose-dependently stimulated by aldosterone in VSMCs. 53 These responses were abrogated by eplerenone and almost abolished by PP2, a selective c-Src inhibitor. Aldosteroneinduced collagen synthesis was significantly reduced by a p38MAP kinase inhibitor.…”
Section: Schiffrinmentioning
confidence: 98%
“…MR is a metabolic nuclear receptor that plays a key role in the regulation of electrolyte homeostasis and blood pressure in the body [12] . MR activation mediates inflammation, proliferation and fibrosis [29,39,40] , while MR blockade exhibits beneficial effects on cardiovascular morbidity and mortality in patients with heart failure [41,42] . Recent studies have also shown that MR antagonists improve adipocyte dysfunction and insulin resistance in obese mice [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Spironolactone (Spir) and eplerenone (Eple), known MR antagonists, have been shown to be useful in the treatment of hypertension and heart failure [29,30] , the reversal of obesity-related changes in pro-inflammatory adipokines and the amelioration of adipocyte dysfunction and insulin resistance [31][32][33] . In addition, the production of pro-inflammatory factors such as TNF-α, MCP-1, and IL-6 was attenuated by Eple both in liver and adipose tissue via the suppression of reactive oxygen species (ROS) [33] , and Spir improved glucose and lipid metabolism by ameliorating inflammation in high-fat and high-fructose diet mice [31] .…”
Section: Introductionmentioning
confidence: 99%